Battling for local phone customers. - Sweet, W.
The long-distance giant AT&T is girding its loins for an attempt to wrest the residential phone customer from local telephone companies around the United States. This paper takes a look at the Midwestern region and evaluates whether its strategy will ?play in Peoria?
Keywords: AT&T.; USA; Local phone customers; Local telephone companies; Residential phone customer